PEMIKIRAN KRITIS SOUND GOVERNANCE TERHADAP GLOBALISASI: PANDANGAN DARI ALI FARAZMAND - Burhanudin Mukhamad Faturahman (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Globalization is an ideology that contributes directly to governance, especially in developing and under developing countries. The governance system suggested by the globalelite, namely good governance that transcends the territorial boundaries of the state, isallegedly causing uncertainty at local, national and regional governance levels. According toAli Farazmand the dimension in sound governance seeks to organize the structure, norms,clear values of management and public administration amidst the diversity and rapidchanges in the international environment.